Four hundred micrograms buccal misoprostol versus five units intravenous oxytocin in prevention of postpartum hemorrhage in elective caesarean section, randomized controlled study - Mitwally, Abo Bakr Abass; Tawfik Mansour, Abanoub Mansour; Ahmed, Abdel-Ghaffar Mohamed (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: The number of studies has been increased about the use of misoprostol during caesarean delivery to prevent obstetric hemorrhage, but may be no study compare buccal misoprostol versus oxytocin in prevention of obstetric hemorrhage during and post cesarean section. Our study is done to compare buccal misoprostol 400 mcg versus oxytocin 5iu intravenous bolus in prevention of postpartum hemorrhage during and post elective cesarean section. Methods: A prospective registered, double blinded, randomized controlled trial Operative list or emergency unit at Obstetrics and Gynecology Department, Women Health Hospital, Assiut university, Egypt, comparing 77 patients in each group after verbal consent. Results: There was significant difference between both groups regarding total amount of blood loss (intra partum plus post-partum) 555.45±74.33 in oxytocin group versus522.6±88.76 in misoprostol group. Conclusions: Buccal misoprostol is more effective than intravenous infusion of oxytocin in reducing blood loss during elective cesarean delivery. However, occurrence of temporary side effects such as fever and chills was more frequent with the use of misoprostol. Clinical trial.gov: NCT03676621.